The global burden and trends analysis of early-onset colorectal cancer attributable to dietary risk factors in 204 countries and territories, 1990–2019: a secondary analysis for the global burden of disease study 2019 - Su, Jiao; Liang, Yuanhao; He, Xiaofeng (Frontiers in Nutrition, 2024)
Background: Rising trends in early-onset colorectal cancer (CRC) burden have been observed, but the distribution and temporal patterns of early-onset CRC attributable to dietary risks remain unclear. Objectives: This study aimed to estimate the burden of early-onset CRC attributable to dietary risk factors globally, regionally, and nationally, by age and sex, from 1990 to 2019. Methods: The absolute number and age-specific rates (ASR) of diet-related early-onset CRC burden, as well as summary exposure value (SEV) of attributable dietary risk factors, were extracted from the Global Burden of Disease (GBD) Study 2019. Results: In 2019, diet-related early-onset CRC caused 30,096 (95% UI: 23,148 to 36,091) death cases and 1,465,755 (95% UI: 1,126,489 to 1,761,661) DALYs worldwide, accounting for 34.8% deaths and 34.4% DALYs of overall early-onset CRC, respectively. Moreover, a diet low in milk (responsible for 16.5% [95% UI: 11.1% to 21.9%] of DALYs in 2019), low in whole grains (15.2% [95% UI: 5.9% to 19.9%]), low in calcium (14.3% [95% UI: 10.7% to 18.9%]), high in red meat (5.3% [95% UI: 1.7% to 9.5%]), high in processed meat (2.5% [95% UI: 0.9% to 4.0%]), and low in fiber (2.3% [95% UI: 0.9% to 4.2%]) were early-onset CRC attributable dietary risk factors. The age-specific DALYs rate of early-onset CRC attributable to each dietary risk factor generally showed an increasing trend globally between 1990 and 2019, except for low intake of fiber (EAPC = −0.57, 95% CI: −0.76 to −0.38). In addition, from 1990 to 2019, males have a higher burden than females and this gap may continue to widen due to the increasing difference between the sexes in most dietary risk factors. Furthermore, dietary risks-attributable early-onset CRC burden has shifted from regions with high socio-demographic index (SDI) to high-middle and middle SDI quintiles with uncontrolled dietary risks. Conclusions: Early-onset CRC remains a concerning issue globally, and effective prevention and modification of dietary risk factors holds great promise to reduce early-onset CRC-related burden. Prioritizing diet improvement for males is critical and urgent for CRC control efforts, particularly for those living in developing countries with ongoing dietary pattern transition.